What future for the European Union? - Matej Avbelj (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2017)
Stimulated by the European Commission's White Paper on the Future of Europe, this article engages critically with the Commission's five scenarios. Driven by a normative ambition of equipping the EU with adequate constitutional, institutional and socio-political means for coping with its many crises, the article argues in favour of the reformist vision of the EU's future. It claims that a new constitutional process for European integration should be launched. On its basis the EU would be reconstituted as a union, a special federal constitutional form, embedded in the normative spirit of pluralism. The article presents the arguments in favour of such a scenario and flashes out the reasons for which the many constitutional actors in the EU, as well as the latter as a whole, could benefit from it. It concludes that in the following few months there might emerge a historical window of opportunity for a qualitative reformist leap in the process of European integration. While the way back to the glorious days of the nation state is effectively closed off and the present status quo in the EU is plainly unsustainable, the article sketches a theoretical framework for the reformed European Union of tomorrow.
Keywords: 320; European Union; European Commission; Future; Constitution-making